2017
DOI: 10.5539/jas.v9n8p208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Levels on Anatomy, Growth, and Chlorophyll Content in Sunflower (Helianthus annuus L.) Leaves

Abstract: Nitrogen nutrition strongly affected the individual leaf expansion, formation and development of palisade and spongy cells, chloroplast membrane organization and number of grana thylakoids, chlorophyll a, and b proportion, chloroplast length and width, epidermal cell division and expansion in sunflower (Helianthus annuus L.) leaves. Nitrogen levels remarkably affected the development of phloem transfer cells, thereby loading and unloading capacity of phloem. Nitrogen nutrition environment exert developmental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…of leaves plant -1 (19.45) and leaf area (1132.00 cm 2 ) was recorded under application of 100% NPK through inorganic fertilizers which was statistically at par with treatment T 3 in which 25% N was applied through VC (Table 1). This could be attributed to higher dose of inorganic nitrogen which is associated with increase in protoplasm, cell division and cell enlargement resulting in taller plants (Kumari, 2017). There was increase in number of leaves with the increase in nitrogen doses because nitrogen promotes the apical branching and hence more number of leaves appeared on plant (Kebrom, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…of leaves plant -1 (19.45) and leaf area (1132.00 cm 2 ) was recorded under application of 100% NPK through inorganic fertilizers which was statistically at par with treatment T 3 in which 25% N was applied through VC (Table 1). This could be attributed to higher dose of inorganic nitrogen which is associated with increase in protoplasm, cell division and cell enlargement resulting in taller plants (Kumari, 2017). There was increase in number of leaves with the increase in nitrogen doses because nitrogen promotes the apical branching and hence more number of leaves appeared on plant (Kebrom, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…De manera que, la aplicación de vinazas, en diferentes grados de dilución, afecta el contenido de nitrógeno foliar, el contenido de clorofilas totales y consecuentemente la asimilación fotosintética. Una tendencia similar se ha encontrado entre el contenido de nitrógeno foliar y la concentración de clorofila para girasol (Kumari, 2017). La disminución del contenido de N f por el agregado de vinazas, podría estar relacionada con el pH ácido de las mismas, lo cual afectaría la población de microorganismos del suelo relacionados con la mineralización del mismo y con ello la descomposición de la materia orgánica, nitrificación (Resende et al, 2006) y denitrificación (Leal et al, 1983.…”
Section: Discussionunclassified
“…Proper vegetative and reproductive growth of the plants was accomplished by a larger amount of nitrogen and phosphorus. Kumari [23] reported that a higher rate of nitrogen is related to an increase in protoplasm, cell division and cell enlargement resulting in better vegetative structure. Hence, Katiya [15] noticed a positive response of phosphorus in the reproductive development of the plant on cauliflower.…”
Section: Plant Weightmentioning
confidence: 99%